2017
DOI: 10.1016/j.brainres.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Striatum on the anxiety map: Small detours into adolescence

Abstract: Adolescence is the most sensitive period for the development of pathological anxiety. Moreover, specific neural changes associated with the striatum might be related to adolescent vulnerability to anxiety. Up to now, the study of anxiety has primarily focused on the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus and ventromedial prefrontal cortex (vmPFC), while the striatum has typically not been considered as part of the anxiety system. This review proposes the addition of the striatum, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 126 publications
(179 reference statements)
6
78
0
Order By: Relevance
“…Besides the amygdala, striatum, hippocampus, hypothalamus and basal forebrain and septum had high fractions of 2-subunit containing diazepam-sensitive GABA A receptors in our PET study. All these regions are suggested to be involved in the neuronal network of anxiety (Lago et al, 2016). Besides the data from the region-of-interest analysis, the images of the voxel-wise mapping of 2-containing receptors are in good agreement with the suggested circuits of anxiety (Lago et al, 2016).…”
Section: Distribution Of 1 2 and 5-containing Diazepam-sensitivesupporting
confidence: 64%
“…Besides the amygdala, striatum, hippocampus, hypothalamus and basal forebrain and septum had high fractions of 2-subunit containing diazepam-sensitive GABA A receptors in our PET study. All these regions are suggested to be involved in the neuronal network of anxiety (Lago et al, 2016). Besides the data from the region-of-interest analysis, the images of the voxel-wise mapping of 2-containing receptors are in good agreement with the suggested circuits of anxiety (Lago et al, 2016).…”
Section: Distribution Of 1 2 and 5-containing Diazepam-sensitivesupporting
confidence: 64%
“…Such adaptations could include a shift of mitochondrial respiration towards (potentially protective) stronger reliance on succinate- / mitochondrial Complex ll-linked respiration (S f ), which is blocked by chronic CORT. Interestingly, the effect size of S E FCR between PFF(C) and PFF groups is comparable to the differences observed in anxiety-like behaviors, behaviors with important striatal participation 66 .…”
Section: Discussionsupporting
confidence: 65%
“…It has been shown that, compared with HC, patients with SAD lack a processing advantage in the putamen for social rewards relative to social punishments ( 92 ). Hence, these findings provided further evidence that structural alterations in the putamen might play a role in the pathophysiology underlying the imbalance in approach-avoidance motivation in SAD [see also ( 93 )].…”
Section: Discussionmentioning
confidence: 68%